Workaholic behaviour in police professionals - MONICA, DR. BENITA. S.; MS. MALINI (The journal of contemporary issues in business and government, 2020)
Workaholism is nothing but working excessive hours beyond workplace or financial requirements, by thinking continually about work, with lack of work enjoyment, which are unrelated to actual workplace demands. This study emphasis on examining the impact of workaholism on work engagement. Convenience sampling method is used to collect the data from 58 police professionals. Multiple linear regression is used to analyse the data. The results prove that the work addiction has negative relationships with work engagement, work life conflict and work perfectionism have positive relationships with work engagement. This study provides suggestions for workaholic people in the police profession.